The effect of waiting queues in improving job performance (Field study in the Civil Status Department in Lattakia Governorate) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The study mainly aimed at determining the effect of waiting queues (service implementation time, number of windows, number of working hours) on improving job performance in Lattakia Governorate.  The researcher followed the analytical descriptive approach in her study, and a set of methods including relying on secondary and primary data through a questionnaire designed and distributed to (140) respondents, from which (135) were retrieved, and (131) questionnaires were valid for analysis, and the research community consisted of a cadre Then, the SPSS program was relied upon as a tool for analyzing the available data.The study reached a set of results, including: the existence of a significant effect of waiting queues in improving job performance in the Civil Status Department, the commitment of workers to the time of service implementation in the Civil Status Department, the presence of a good number of windows in the Civil Status Department, the number of working hours is good in the department in place Study, a relative increase in the quality of work, and the amount of work done is large in the department under study.